2022
DOI: 10.3389/ffgc.2022.742157
|View full text |Cite
|
Sign up to set email alerts
|

The Legacy of Hurricanes, Historic Land Cover, and Municipal Ordinances on Urban Tree Canopy in Florida (United States)

Abstract: Urban Tree Canopy (UTC) greatly enhances the livability of cities by reducing urban heat buildup, mitigating stormwater runoff, and filtering airborne particulates, among other ecological services. These benefits, combined with the relative ease of measuring tree cover from aerial imagery, have led many cities to adopt management strategies based on UTC goals. In this study, we conducted canopy analyses for 300 cities in Florida to assess the impacts of development practices, urban forest ordinances, and hurri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…More recently, Hilbert et al (2019) found that Florida (United States) cities with heritage tree protections had more tree canopy compared to peer cities lacking these protections. When this research was expanded to incorporate more communities (n=300) and account for external factors like hurricanes, a similar benefit was observed (Salisbury, 2022).…”
Section: Introductionmentioning
confidence: 56%
“…More recently, Hilbert et al (2019) found that Florida (United States) cities with heritage tree protections had more tree canopy compared to peer cities lacking these protections. When this research was expanded to incorporate more communities (n=300) and account for external factors like hurricanes, a similar benefit was observed (Salisbury, 2022).…”
Section: Introductionmentioning
confidence: 56%
“…Throughout the world, urban developments are concentrated in coastal areas, many of which are exposed to intense wind events (e.g., hurricanes, cyclones, and typhoons) [1] that can induce failure of whole trees, branches, trunks, or roots. Previous work has investigated wind-induced tree failures in natural areas and on plantations [2][3][4][5][6][7][8] as well as in urban areas [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…One study, for example, which relied on responses and measurements by homeowners, found urban forest loss between 13% for Hurricane Georges (1998) in Puerto Rico and 16% for Hurricane Charley (2004) in Florida, where palms survived significantly better than all other trees [25]. Another study found that peak gust speeds recorded during past hurricane events were negatively associated with canopy coverage across the 300 most populated municipalities in Florida [26].…”
Section: Introductionmentioning
confidence: 99%